Incidence and management of foreign bodies in aerodigestive tract in a tertiary level - Neetu Bajaj; Dharmendra Kanoriya (International Journal of Medical Research and Review, 2019)
Introduction: Foreign body (FB) ingestion and aspiration is a life-threatening condition which is quite common in children. It is important to diagnose foreign body aspiration early as delay in its recognition and treatment results in high morbidity and mortality. The objective of the present prospective study was to study foreign bodies in aerodigestive tract on the basis of history, examination, and investigation, their incidence, type of foreign body, site of lodgment, common symptoms with which presented, and the nature of the problem in dealing with these patients during the management.Materials and Methods: A total of 86 cases of FB in aerodigestive tract admitted in ENT ward of Bundelkhand Medical and Hospital were included in the study. The symptoms, site and radiographic findings were recorded for each patient. Various procedures were used for removal of various FB at different locations. Majority of these procedures were performed under anesthesia.Results: Of all admitted foreign body cases (86 cases), incidence was more for males (63 cases) than for females (23 cases). Likewise, it was encountered more commonly in the age group of 1-10 years. FB were removed smoothly and successfully in all cases. Overall outcome was excellentwith minimum morbidity and no mortality. According to the site of involvement, hospital stay was varied.Conclusion: In this study, it is evident that FB in aerodigestive tract is a common clinical problem in otorhinolaryngological practice. Although, some presents with serious and life-threatening emergencieswhilemany does not have an immediate problem of airway. Higher incidence of foreign body in children can be prevented by educating the parents about keeping the articleaway from reach of children and observing the activity of the child.